Species occurrence of the potentially toxigenic diatom genus Pseudo-nitzschia and the associated neurotoxin domoic acid in the Argentine Sea - Almandoz, Gastón Osvaldo (2017)
The marine diatom genus Pseudo-nitzschia, the major known producer of the neurotoxin domoic acid (DA) responsible for the amnesic shellfish poisoning (ASP) syndrome in humans and marine mammals, is globally distributed. The genus presents high species richness in the Argentine Sea and DA has been frequently detected in the last few years in plankton and shellfish samples, but the species identity of the producers remains unclear. In the present work, the distribution and abundance of Pseudo-nitzschia species and DA were determined from samples collected on two oceanographic cruises carried out through the Argentine Sea (⁓39–47ºS) during summer and spring 2013. Phytoplankton composition was analysed by light and electron microscopy while DA was determined by liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS). The genus Pseudo-nitzschia was recorded in 71 and 86% of samples collected in summer and spring, respectively, whereas DA was detected in only 42 and 21% of samples, respectively. Microscopic analyses revealed at least five potentially toxic species (P. australis, P. brasiliana, P. fraudulenta, P. pungens, P. turgidula), plus putatively non-toxigenic P. dolorosa, P. lineola, P. turgiduloides and unidentified specimens of the P. pseudodelicatissima complex. The species P. australis showed the highest correlation with DA occurrence (r = 0.55; p < 0.05), suggesting its importance as a major DA producer in the Argentine Sea. In the northern area and during summer, DA was associated with the presence of P. brasiliana, a species recorded for the first time in the Argentine Sea. By contrast, high concentrations of P. fraudulenta, P. pungens and P. turgidula did not correspond with DA occurrence. This study represents the first successful attempt to link toxigenicity with Pseudo-nitzschia diversity and cell abundance in field plankton populations in the south-western Atlantic.